Preparation method and application of skeleton nickel doped TS-1 type molecular sieve catalyst

By introducing nickel cations into the molecular sieve framework using nickel ion coordination complexing in TS-1 titanium silicon molecular sieve, the problem of nickel in the form of oxide particles is solved, and the performance and stability of the catalyst are improved. It is suitable for multiple industrial catalytic reaction.

CN119318992APending Publication Date: 2025-01-17INST OF METAL RESEARCH - CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411272438.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing preparation method of TS-1 titanium silicon molecular sieve has problems such as difficult control, high cost, large grain size and uneven distribution. In the nickel doping method, nickel exists in the form of oxide particles, which cannot effectively improve catalytic performance.

Method used

The TS-1 titanium silicon molecular sieve raw powder was prepared by using cheap raw materials. The nickel ion coordination complex combined with tetrapropyl ammonium hydroxide hydrothermal treatment was introduced into the molecular sieve skeleton to form a hollow cavity, and nickel ions were embedded in the molecular sieve skeleton. , ensure that nickel is evenly distributed in cationic form.

Benefits of technology

It significantly improves the activity and stability of the catalyst, optimizes the surface acidic site structure and the electron cloud density around titanium, improves the catalytic performance and coking resistance, and is suitable for a variety of industrial catalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318992A_ABST
    Figure CN119318992A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts and application thereof, and particularly relates to a preparation method and application of a framework nickel-doped TS-1 type molecular sieve catalyst. According to the method, TS-1 titanium silicalite molecular sieve raw powder prepared from cheap raw materials is adopted as an initial raw material, nickel cations are introduced into a TS-1 molecular sieve framework in a mode of combining nickel ion coordination complexation with tetrapropylammonium hydroxide hydrothermal treatment, and a hollow cavity is formed in a molecular sieve crystal. The protective effect of the complexing agent on nickel ions effectively prevents the nickel ions from forming metal nickel particles in the hydrothermal treatment process; the tetrapropylammonium hydroxide promotes the TS-1 titanium silicalite molecular sieve to be dissolved and recrystallized to form closed or open mesopores, and nickel ions are embedded into a molecular sieve framework. In the prepared nickel-doped TS-1 titanium silicalite molecular sieve, nickel exists in the form of positive ions and partially replaces titanium ions in a framework, so that the charge density around the titanium ions is remarkably reduced, and the surface acidity is weakened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and their applications, and specifically is a preparation method and application of a skeleton nickel-doped TS-1 type molecular sieve catalyst. Background Art

[0002] In 1983, Taramasso first reported in patent US4410501 a method for synthesizing TS-1 titanium silicalite (abbreviated as TS-1) by hydrothermal crystallization. This classic method is carried out under nitrogen protection and CO2-free atmosphere, and requires the use of high-purity and large amounts of tetrapropylammonium hydroxide (TPAOH) as a template. Although this method can successfully synthesize TS-1 titanium silicalite, it has the following problems: (1) The hydrolysis and nucleation conditions are difficult to control, resulting in low catalytic activity and poor repeatability of the synthesized molecular sieve; (2) The raw material purity requirements are high, especially the large amount of TPAOH, which leads to high production costs.

[0003] In 1992, Thangaraj et al. proposed an improved method, using tetrabutyl titanate (TBOT) with weaker hydrolysis activity as a titanium source to increase the content of skeleton titanium in TS-1. However, this method still requires the use of high-purity raw materials and a large amount of TPAOH, and the cost is still high.

[0004] In order to reduce the cost of synthesis, people have developed a variety of methods to replace TPAOH with cheap templates (such as tetrapropylammonium bromide, tetraethylammonium hydroxide, hexamethyleneimine, piperidine, etc.). However, due to the low concentration of OH- ions in the synthesis system, the crystallization process of TS-1 is slow, the synthesized grain size is large (>10 microns), and the catalytic activity is low.

[0005] By adding nano-TS-1 titanium silicon molecular sieve seeds to the cheap system, the nucleation of the molecular sieve can be promoted, the induction time can be reduced, the crystallization rate can be increased, and the crystal size can be reduced. However, even with the addition of seeds, the molecular sieve crystals synthesized by the cheap system are still larger than the molecular sieve crystals obtained by using tetrapropylammonium hydroxide as a template in the classical method (greater than 500 nanometers), and the catalytic performance is still far behind the TS-1 titanium silicon molecular sieve prepared by the classical method, which limits the industrial application of TS-1 molecular sieves prepared by cheap raw materials.

[0006] In summary, the existing preparation methods of TS-1 titanium silicalite, whether it is the classical method, the improved method or the low-cost synthesis method, all have problems such as difficult control, high cost, large grain size and uneven distribution. These problems limit the application and promotion of TS-1 molecular sieve in industrial catalysis. Therefore, it is necessary to further study and develop new synthesis methods to solve the above problems and improve the performance and economy of TS-1 titanium silicalite.

[0007] Doping nickel in TS-1 molecular sieve can significantly change the surface acidic site structure and the electron cloud density around titanium, thereby improving the catalytic performance. First, the introduction of nickel neutralizes the surface acidic sites and inhibits over-oxidation reactions. This change improves the selectivity and efficiency of the catalyst and helps the precise conduct of the catalytic reaction. Secondly, nickel reduces the electron cloud density around titanium, enhances the electrophilicity of the titanium active center, and is conducive to the formation of active intermediates and the conduct of catalytic reactions. This change in the electronic environment promotes the combination of Ti(IV) and hydrogen peroxide (H2O2) to generate Ti-OOH active intermediates and improve the efficiency of the oxidation reaction. In addition, nickel doping also neutralizes the surface acidic sites, reduces carbon deposition, enhances anti-coking ability, and prolongs the service life of the catalyst. These optimization effects enable nickel-doped TS-1 titanium silicon molecular sieve to exhibit excellent performance in a variety of industrial catalytic reactions, with broad application prospects and important industrial value.

[0008] At present, the methods of nickel doping TS-1 titanium silicon molecular sieve mainly include mechanical mixing method and impregnation method. The presence of nickel in the above two methods has a significant effect on the surface acidic site structure of TS-1 and the electron cloud density around titanium. The following is a detailed comparison of the effect of nickel presence on the surface acidic site structure of TS-1 titanium silicon molecular sieve and the electron cloud density around titanium:

[0009] (1) Doping by mechanical mixing: Nickel usually exists in the form of metal or oxide particles and is unevenly distributed. Nickel doped by mechanical mixing easily forms metallic nickel or nickel oxide particles, which will not significantly change the acidic site structure on the TS-1 surface. Since nickel particles cannot be evenly distributed in the molecular sieve framework, they cannot effectively neutralize the acidic sites on the surface, resulting in the acidic site structure not being optimized. Nickel particles mainly exist on the surface or in the pores of the molecular sieve, and the electron cloud density around titanium does not change significantly. Nickel particles cannot effectively interact with titanium sites, making it difficult to improve the electrophilicity of titanium active centers.

[0010] (2) Doping by impregnation method: Nickel exists in the form of nickel oxide, which is relatively evenly distributed, but the particles are larger. The nickel ions doped by the impregnation method are easily reduced to metallic nickel during the calcination process to form larger nickel particles. These particles have limited effect on the acidic site structure on the surface of TS-1 and cannot effectively neutralize the excess acidic sites. Acidic centers still exist, affecting the catalytic performance. The metallic nickel particles formed after high-temperature reduction or the nickel oxide particles formed by high-temperature oxidation have limited effect on changing the electron cloud density around titanium. Since nickel cannot be evenly distributed in the molecular sieve framework, the electrophilicity of the titanium active center is limited.

[0011] In summary, from the perspective of the effect of the nickel presence on the surface acidic site structure of TS-1 titanium silicon molecular sieve and the electron cloud density around titanium, the existing nickel doping method has limited effect on the surface acidic site structure of TS-1 titanium silicon molecular sieve and the electron cloud density around titanium because nickel exists on the surface of the molecular sieve or in the pores in the form of oxide particles, and cannot effectively improve the catalytic performance of TS-1 titanium silicon molecular sieve. The future development trend is to incorporate nickel into the molecular sieve framework and ensure that nickel is evenly distributed in the molecular sieve in the form of cations, thereby optimizing the surface acidic site structure of TS-1 and the electron cloud density around titanium, and improving the performance and stability of the catalyst. Summary of the invention

[0012] The purpose of the present invention is to provide a preparation method and application of a skeleton nickel-doped TS-1 type molecular sieve catalyst, so as to solve the problems in the prior art that nickel exists on the surface or in the pores of the molecular sieve in the form of oxide particles, which has limited effect on the surface acidic site structure of the TS-1 titanium silicon molecular sieve and the electron cloud density around titanium, and cannot effectively improve the catalytic performance of the TS-1 titanium silicon molecular sieve. By optimizing the surface acidic site structure of TS-1 and the electron cloud density around titanium, the activity and stability of the catalyst in the green catalytic oxidation reaction are improved.

[0013] The technical solution of the present invention is:

[0014] A method for preparing a TS-1 molecular sieve catalyst doped with skeleton nickel, wherein the method uses TS-1 titanium silicon molecular sieve raw powder prepared from cheap raw materials as an initial raw material, introduces nickel cations into the TS-1 molecular sieve skeleton by means of nickel ion coordination complexation combined with tetrapropylammonium hydroxide hydrothermal treatment, and forms a hollow cavity inside the molecular sieve crystal; the tetrapropylammonium hydroxide promotes the dissolution and recrystallization of the TS-1 titanium silicon molecular sieve to form closed or open mesopores, and enables nickel ions to be embedded in the molecular sieve skeleton.

[0015] The preparation method of the skeleton nickel-doped TS-1 type molecular sieve catalyst comprises the following steps: 1) adding TS-1 titanium silicon molecular sieve raw powder to a mixed solution of deionized water and tetrapropylammonium hydroxide, wherein the molar ratio of tetrapropylammonium hydroxide to deionized water is 1:1000-1:50, and the mass ratio of TS-1 titanium silicon molecular sieve raw powder to the mixed solution is 1:5-1:50; 2) adding a nickel source protected by a complexing agent, wherein the molar ratio of the nickel source to the complexing agent is 1:0.1-1:10; 3) pouring the above mixture into a reactor, and subjecting it to hydrothermal treatment at 150-180°C for 24-72 hours; 4) cooling the reactor to room temperature, centrifuging, washing, drying and roasting to obtain the product.

[0016] In the method for preparing the skeleton nickel-doped TS-1 molecular sieve catalyst, preferably, the molar ratio of tetrapropylammonium hydroxide to deionized water is 1:1 to 1:30.

[0017] The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst preferably has a molar ratio of nickel source to complexing agent of 1:0.2 to 1:5, and the nickel source used is one or more of nickel sulfate, nickel phosphate, nickel nitrate, nickel acetate, nickel chloride, and nickel carbonate; the complexing agent used is one or more of ethylenediamine, diethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, hexamethylenediamine, and polyethylenepolyamines.

[0018] The preparation method of the skeleton nickel-doped TS-1 type molecular sieve catalyst comprises cheap raw materials: the template agent is tetrapropylammonium bromide, the titanium source is one or more of tetrabutyl titanate, tetraisopropyl titanate, titanium sulfate, titanium tetrachloride or titanium trichloride, the silicon source is at least one of water glass, silica gel and silica sol, and the alkali source is an organic amine, including at least one of ammonia water, methylamine, ethylamine, ethylenediamine, diethylamine, triethylamine, propylamine, n-butylamine and hexamethylenediamine.

[0019] The preparation method of the skeleton nickel-doped TS-1 type molecular sieve catalyst uses cheap raw materials to prepare the TS-1 titanium silicon molecular sieve raw powder as follows: first, after deionized water, tetrapropylammonium bromide and organic amine are mixed evenly, a silicon source is added dropwise, and stirring is continued until the solution is clarified and uniform, and then a titanium source is added and stirred to form a clarified mixed solution; then, a titanium silicon molecular sieve precursor dry gel containing original zeolite units, or nano-scale TS-1 titanium silicon molecular sieve seeds, or a titanium silicon molecular sieve precursor solution is added, and the mixture is transferred to a high-pressure reactor with a polytetrafluoroethylene liner, and crystallized at 130-170°C for 12-48 hours; after the reactor is cooled to room temperature, the product is obtained by centrifugation, washing, drying and roasting; wherein the molar ratio of tetrapropylammonium bromide to silicon source is less than 0.05, and the content of titanium silicon molecular sieve precursor in the titanium silicon molecular sieve precursor dry gel containing original zeolite units, the nano-scale TS-1 titanium silicon molecular sieve seeds or the titanium silicon molecular sieve precursor solution is 5-20wt%.

[0020] The method for preparing the skeleton nickel-doped TS-1 molecular sieve catalyst comprises the following steps: in the TS-1 titanium silicon molecular sieve raw powder, the crystal size of the TS-1 titanium silicon molecular sieve is 150 nanometers to 800 nanometers, and the silicon-titanium atomic ratio is 20 to 200.

[0021] The preparation method of the skeleton nickel-doped TS-1 type molecular sieve catalyst, in the nickel-doped TS-1 titanium silicon molecular sieve, the nickel content in the molecular sieve crystal is 0.01-5wt%, the titanium content is 0.01-2.5wt%, the nickel exists in the form of cations, partially replaces the titanium ions in the skeleton, reduces the charge density around the titanium ions, and weakens the surface acidity.

[0022] The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst is as follows: the prepared nickel-doped TS-1 titanium silicon molecular sieve has a b-axis oriented flaky single crystal structure, has no inter-growth twins, has a small crystal size of 150 nanometers to 800 nanometers; the molecular sieve crystal has closed or open mesopores in addition to intrinsic micropores, and the micropore volume is 0.10 to 0.20 cm 3 ·g -1 , the mesopore volume is 0.10~0.50cm 3 ·g -1 .

[0023] The application of the skeleton nickel-doped TS-1 type molecular sieve catalyst shows excellent activity, anti-coking ability and recycling performance in olefin epoxidation, phenol oxidation, aromatic hydrocarbon hydroxylation, ketone ammoxidation, alkane partial oxidation or alcohol partial oxidation reactions, which is beneficial to mass transfer and improving catalytic efficiency.

[0024] The design concept of the present invention is:

[0025] The present invention adopts TS-1 titanium silicon molecular sieve raw powder prepared from cheap raw materials as the initial raw material, and introduces nickel cations into the TS-1 molecular sieve framework and forms a hollow cavity inside the molecular sieve crystal by means of nickel ion coordination complexation combined with tetrapropylammonium hydroxide hydrothermal treatment. The protective effect of the complexing agent on nickel ions effectively prevents the nickel ions from forming metal nickel particles during the hydrothermal treatment process; tetrapropylammonium hydroxide promotes the dissolution and recrystallization of the TS-1 titanium silicon molecular sieve to form closed or open mesopores, and embeds nickel ions into the molecular sieve framework. In the prepared nickel-doped TS-1 titanium silicon molecular sieve, nickel exists in the form of cations, partially replaces the titanium ions in the framework, significantly reduces the charge density around the titanium ions, and weakens the surface acidity. At the same time, the molecular sieve has a b-axis oriented single crystal structure, and the molecular sieve crystal has closed or open mesopores in addition to intrinsic micropores, so that it has good hydrothermal stability and good intracrystalline mass transfer performance, so that it exhibits excellent activity, anti-coking ability and recycling performance in catalytic oxidation reactions.

[0026] In the nickel-doped TS-1 titanium silicon molecular sieve of the present invention, nickel exists in the form of cations, partially replaces the titanium ions in the framework, significantly reduces the charge density around the titanium ions, and weakens the surface acidity. In the process of hydrothermal treatment of the TS-1 molecular sieve with tetrapropylammonium hydroxide, the protective effect of the complexing agent on the nickel ions effectively prevents the nickel ions from forming metal nickel particles during the hydrothermal treatment; tetrapropylammonium hydroxide promotes the dissolution and recrystallization of the TS-1 titanium silicon molecular sieve, forms closed or open mesopores between the intrinsic micropores of the molecular sieve crystal, and embeds the nickel ions into the molecular sieve framework. In the molecular sieve, nickel exists in the form of cations, partially replaces the titanium ions in the framework, significantly reduces the charge density around the titanium ions, weakens the surface acidity, and has good mass transfer performance; the molecular sieve is a b-axis oriented single crystal, and in addition to having intrinsic micropores, it also has a closed or open mesoporous structure, which is conducive to mass transfer and improves catalytic efficiency in olefin epoxidation, phenol oxidation, aromatic hydrocarbon hydroxylation, ketone ammoxidation, partial oxidation of alkanes or partial oxidation of alcohols.

[0027] The present invention has the following advantages and beneficial effects:

[0028] (1) Method and innovation of introducing nickel cations: The coordination complex protection method is used to introduce nickel cations into the TS-1 titanium silicalite framework during the hydrothermal treatment with tetrapropylammonium hydroxide, which is significantly innovative. First, the coordination complexing agent can effectively prevent nickel from being reduced to metal particles or forming nickel oxide particles during high-temperature hydrothermal treatment, ensuring that nickel is evenly distributed in the molecular sieve framework in the form of cations. Secondly, this method can efficiently introduce nickel cations into the molecular sieve framework, ensuring that nickel exists in the form of cations and partially replaces titanium ions in the framework, thereby significantly reducing the electron cloud density around titanium, enhancing the electrophilicity of the titanium active center, and optimizing the acidic site structure.

[0029] (2) The key role of tetrapropylammonium hydroxide: Tetrapropylammonium hydroxide not only acts as a template, but also plays a key role in the nickel doping process. First, it promotes the dissolution and recrystallization of TS-1 titanium silicalite during the hydrothermal treatment process, forming closed or open mesopores between the intrinsic micropores of the molecular sieve, significantly improving the diffusion performance of the molecular sieve, reducing the diffusion resistance, and further improving the catalytic efficiency.

[0030] (3) Significant improvement in catalytic performance: The nickel-doped TS-1 titanium silicalite prepared by the above method shows significant advantages in catalytic performance. Nickel cations are evenly distributed in the molecular sieve framework, reducing surface acidity, enhancing anti-coking ability, and enabling the catalyst to maintain high catalytic activity under high temperature conditions. At the same time, the optimized acidic site structure and electronic environment, as well as the better pore structure, make the nickel-doped TS-1 titanium silicalite have excellent catalytic activity, anti-coking ability and recycling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a transmission electron microscope image of TS-1 titanium silicon molecular sieve powder prepared using cheap raw materials in the present invention.

[0032] Figure 2 : (a) is a transmission electron microscope image of nickel-doped TS-1 titanium silicon molecular sieve prepared by tetrapropylammonium hydroxide post-treatment combined with coordination complex method in Example 1 of the present invention; (b) is a local magnified image; (c) is the EDS energy spectrum element surface scanning result.

[0033] Figure 3 This is a transmission electron microscope image of the molecular sieve obtained after the TS-1 titanium silicon molecular sieve prepared from the cheap raw materials in Comparative Example 1 was post-treated with tetrapropylammonium hydroxide.

[0034] Figure 4 : (a) is a transmission electron microscope image of the nickel-doped TS-1 titanium silicon molecular sieve synthesized by mechanical grinding method in Comparative Example 2; (b) is a local enlarged view.

[0035] Figure 5 : (a) is a transmission electron microscope image of the nickel-doped TS-1 titanium silicon molecular sieve synthesized by the impregnation method in Comparative Example 3; (b) is a local enlarged view.

[0036] Figure 6 : (a) is the X-ray diffraction spectrum of TS-1 titanium silicalite synthesized in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention; (b) is a local enlarged view.

[0037] Figure 7 Fourier infrared diffuse reflectance spectra of TS-1 titanium silicalite synthesized in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.

[0038] Figure 8(a) is the X-ray photoelectron spectra of TS-1 titanium silicon molecular sieve synthesized in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. Figure 8(b) is the Ti 2p peak, and Figure 8(c) is the Ni 2p peak.

[0039] Fig. 9 This is the hydrogen temperature-programmed reduction spectra of the TS-1 titanium silicon molecular sieve synthesized in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention.

[0040] Fig.10 The ultraviolet spectra of TS-1 titanium silicalite molecular sieves synthesized in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0041] In the specific implementation process, the process of preparing TS-1 titanium silicon molecular sieve raw powder using cheap raw materials is as follows:

[0042] (1) Preparation of molecular sieve precursor dry gel containing original zeolite:

[0043] After tetrapropylammonium hydroxide and deionized water are evenly mixed, ethyl orthosilicate is added dropwise. After ethyl orthosilicate is completely hydrolyzed until it is clear and uniform, tetrabutyl titanate is added and stirred to form a clear mixed solution. The molar ratio of ethyl orthosilicate, tetrapropylammonium hydroxide, tetrabutyl titanate and deionized water in the mixed solution is 1:0.32:0.03:19. After the above mixed solution is condensed and refluxed at 80°C for 8 hours, it is poured into a beaker and stirred at 50°C to remove part of the water to obtain a molecular sieve precursor dry gel with a water content of 20wt%. The dry gel is crushed into 20-30 mesh particles for standby use.

[0044] (2) Synthesis of TS-1 titanium silicate molecular sieve using cheap raw materials:

[0045] First, deionized water, tetrapropylammonium bromide and ethylamine are mixed evenly, and silica sol is slowly added dropwise. After stirring until the solution is clear and uniform, titanium tetrachloride is added and stirred into a clear mixed solution. The molar ratio of silica sol, titanium tetrachloride, tetrapropylammonium bromide, ethylamine and deionized water in the mixed solution is 1:0.03:0.03:0.8:30. Then, molecular sieve precursor dry glue is added to the above mixed solution, and the amount of dry glue added is 8wt%. The mixture is transferred to a high-pressure reactor with a polytetrafluoroethylene liner and crystallized at 160°C for 12 hours. After the reaction is completed, the reactor is cooled to room temperature, centrifuged, washed, dried and calcined to obtain the product.

[0046] Below, the present invention is further described in detail by examples.

[0047] Example 1

[0048] In this embodiment, a method for preparing nickel-doped TS-1 titanium silicon molecular sieve by post-treatment with tetrapropylammonium hydroxide combined with a coordination complex method is mainly provided.

[0049] First, 0.2 mol / L nickel nitrate hexahydrate (Ni(NO3)2·6H2O) aqueous solution and 0.2 mol / L tetraethylenepentamine (TEPA) aqueous solution were mixed in a volume ratio of 1:1 as a nickel ion precursor. Then, 4.5 mL of the nickel ion precursor was mixed with 20 mL of 0.4 mol / L TPAOH aqueous solution and 2 grams of TS-1 titanium silicon molecular sieve powder prepared from cheap raw materials, and then transferred to a high-pressure reactor for hydrothermal crystallization at 180°C for 48 hours. The obtained sample was centrifuged, washed, dried, and calcined at 550°C for 6 hours to obtain nickel-doped TS-1 titanium silicon molecular sieve, which was recorded as CSD@HTS-1.

[0050] Comparative Example 1

[0051] In this embodiment, a method for preparing TS-1 titanium silicalite molecular sieve by post-treatment of tetrapropylammonium hydroxide is mainly provided.

[0052] 2 g of TS-1 titanium silicalite powder prepared from cheap raw materials was added to 20 mL of 0.6 mol / L TPAOH aqueous solution, and after being evenly dispersed, it was transferred to a high-pressure reactor for hydrothermal crystallization at 180°C for 48 hours. The obtained sample was centrifuged, washed, dried, and calcined at 550°C for 6 hours to obtain TS-1 titanium silicalite modified by tetrapropylammonium hydroxide post-treatment, which was recorded as HTS-1.

[0053] Comparative Example 2

[0054] In this embodiment, a method for preparing nickel-doped TS-1 titanium silicon molecular sieve by mechanical grinding is mainly provided.

[0055] 0.15 g of solid Ni(NO3)2·6H2O and 2 g of HTS-1 powder prepared in Comparative Example 1 were fully ground in a ball mill. Subsequently, the mixture was calcined at 550°C for 6 hours to obtain nickel-doped TS-1 titanium silicon molecular sieve, which was recorded as GR@HTS-1.

[0056] Comparative Example 3

[0057] In this embodiment, a method for preparing nickel-doped TS-1 titanium silicon molecular sieve by impregnation method is mainly provided.

[0058] 8 mL of 0.2 mol / L Ni(NO3)2·6H2O aqueous solution was added to 20 mL of deionized water, and then 2 grams of HTS-1 powder prepared by the method in Comparative Example 1 was dispersed into the solution. The mixture was stirred at room temperature for 2 hours to allow the nickel ions to be fully adsorbed by the titanium silicon molecular sieve. After impregnation, the solid and liquid phases were separated by centrifugation and dried at 100°C overnight. Subsequently, the dried powder was calcined at 550°C for 6 hours to obtain nickel-doped TS-1 titanium silicon molecular sieve, recorded as IM@HTS-1.

[0059] The catalytic performance of the TS-1 titanium silicalite synthesized in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention was evaluated by using phenol hydroxylation to produce hydroquinone as a probe reaction. The experimental steps are as follows:

[0060] The reaction was carried out in a 100 mL double-necked round-bottom flask equipped with a reflux condenser. Catalyst TS-1 (200 mg), deionized water (10 mL), and phenol (2 g) were added in sequence. The mixture was heated to 80°C in a constant temperature oil bath and maintained for a period of time. Then, H2O2 (720 μL; the molar ratio of phenol to H2O2 was 3:1) was added. After reacting for different times, the liquid product was aspirated and extracted with ethyl acetate. An appropriate amount of the upper organic extract phase was taken and analyzed using a gas chromatograph (GC-Agilent8890) equipped with a 30 m capillary column (HP-5) and a FID detector.

[0061] Comparative analysis of the physical and chemical properties of the TS-1 titanium silicalite molecular sieves synthesized in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention.

[0062] like Figure 1 As shown in FIG. 1 , the transmission electron microscope image of the TS-1 titanium silicon molecular sieve raw powder prepared using cheap raw materials in the present invention. Figure 3 As shown in Figure 1, the transmission electron microscope image of TS-1 titanium silicon molecular sieve prepared using the same cheap raw materials after being post-treated with tetrapropylammonium hydroxide in Comparative Example 1. Figure 1 and Figure 3 It can be seen that the TS-1 titanium silicon molecular sieve powder prepared from cheap raw materials has a single crystal structure with b-axis orientation and a crystal size of about 600 nanometers. After post-treatment with tetrapropylammonium hydroxide, the size and macroscopic structure of the crystal did not change significantly, but closed or open mesopores appeared inside the crystal, which is consistent with the results reported in the literature that tetrapropylammonium hydroxide produces closed or open mesoporous structures inside TS-1 titanium silicon molecular sieve crystals.

[0063] like Figure 2 (a)-(b) show transmission electron microscope images of nickel-doped TS-1 titanium silicon molecular sieve prepared by tetrapropylammonium hydroxide post-treatment combined with coordination complexation method in Example 1 of the present invention. It can be seen that closed or open mesopores are also formed inside the nickel-doped TS-1 titanium silicon molecular sieve crystal prepared by this method, and no nickel oxide particles are found inside or on the surface of the crystal. Figure 2 (c) shows the EDS spectrum component analysis results of nickel-doped TS-1 titanium silicon molecular sieve. From the EDS spectrum, it can be seen that the molecular sieve crystal contains nickel element.

[0064] like Figure 4 As shown, the transmission electron microscope image of the nickel-doped TS-1 titanium silicon molecular sieve synthesized by mechanical grinding method in Comparative Example 2. From the figure, it can be seen that nickel oxide particles with a size of tens of nanometers are attached to the surface of the molecular sieve crystal.

[0065] like Figure 5As shown, the transmission electron microscope image of the nickel-doped TS-1 titanium silicon molecular sieve synthesized by the impregnation method in Comparative Example 3. It can be observed that a large number of nickel oxide particles with a size of several nanometers are generated on the surface of the molecular sieve crystal.

[0066] From the results of transmission electron microscopy characterization, it can be seen that the TS-1 titanium silicalite prepared from cheap raw materials maintains the original b-axis oriented single crystal structure and macroscopic size after post-treatment with tetrapropylammonium hydroxide, but closed or open mesopores appear inside the crystal. The nickel-doped TS-1 titanium silicalite prepared by post-treatment with tetrapropylammonium hydroxide combined with coordination complexation also produces closed or open mesopores, and no nickel oxide particles are found inside or on the surface of the crystal. In contrast, nickel oxide particles of different sizes are formed on the surface of the crystal in the nickel-doped TS-1 titanium silicalite samples synthesized by mechanical grinding and impregnation.

[0067] like Figure 6 As shown, the XRD spectra of the samples prepared in Example 1 and Comparative Examples 2, 3, and 4 are shown. The nickel-doped samples maintained the MFI structure at 7.8°, 8.8°, 22.9°, 23.8°, and 24.3°, indicating that nickel doping had no significant effect on the molecular sieve structure. However, at 43.2°, obvious nickel oxide characteristic peaks appeared in the IM@HTS-1 and GR@HTS-1 samples, while no nickel oxide characteristic peaks were found in the XRD spectrum of the CSD@HTS-1 sample. This shows that the nickel in the mechanical grinding and impregnation methods exists in the form of nickel oxide, while the CSD@HTS-1 method exists in the form of molecular sieve framework cationic nickel.

[0068] like Figure 7 As shown, the Fourier transform infrared spectra of TS-1 titanium silicon molecular sieve powder prepared from original cheap raw materials, Example 1 and Comparative Examples 1, 2, and 3. All samples have a peak intensity of 450, 550, 800, 960, 1073, and 1232 cm -1 The characteristic peaks are consistent with the characteristics of MFI structure, indicating that the sample retains the structure of MFI type titanium silicalite molecular sieve. -1 The absorption peak at 960 cm is caused by the vibration of Si-O-Ti or Ti-O-Si bonds. In the CSD@HTS-1 sample, this absorption peak is significantly weakened, indicating that there is an interaction between nickel and titanium or nickel replaces part of the framework titanium, resulting in a weakening of the vibration intensity of the [Ti-O] bond. Compared with other nickel-doped samples, these samples have a strong absorption peak at 960 cm-1, because nickel exists in the form of nickel oxide loaded on the surface of the molecular sieve. -1 This further indicates that in the CSD@HTS-1 sample, nickel is highly dispersed inside the titanium silicon molecular sieve and forms a strong interaction with titanium, while in other samples, nickel mainly exists on the surface in the form of nickel oxide and does not form a significant interaction with the framework titanium.

[0069] In summary, the Fourier transform infrared spectroscopy results show that although all samples retain the structure of MFI-type titanium silicalite, in the Ni@HTS-1 sample, the 960 cm -1 The absorption peak at is significantly weakened. This indicates that nickel is highly dispersed in CSD@HTS-1 and forms a strong interaction with titanium, while nickel in other nickel-doped samples mainly exists in the form of surface nickel oxide and does not show significant interaction.

[0070] As can be seen from Figure 8(a) and Table 1, although the nickel loading of each sample is similar (ICP test results are all close to 1.7wt%), there are significant differences in the surface Ni content. CSD@HTS-1 has the lowest surface Ni content, only 0.35wt%, which is significantly lower than IM@HTS-1 (1.94wt%) and GR@HTS-1 (2.23wt%). This difference indicates that in CSD@HTS-1, nickel is highly dispersed inside the titanium silicon molecular sieve, while in IM@HTS-1 and GR@HTS-1, nickel is mainly enriched on the surface of the molecular sieve. The Ni 2p XPS spectra of Comparative Examples 2 and 3 samples show two main peaks, corresponding to the 2p 3 / 2 and 2p 1 / 2 core energy levels of nickel oxide and their vibration satellite peaks. No obvious peak is seen around 852.4eV, indicating that nickel does not exist in the form of metal in these nickel-loaded catalysts.

[0071] As can be seen from Figure 8(b), the binding energy of IM@HTS-1 is slightly lower than that of GR@HTS-1, while the binding energy of CSD@HTS-1 is the lowest. This indicates that there is an electron cloud interaction between the titanium atoms and the nickel atoms in the micropores, and this interaction is the strongest in CSD@HTS-1.

[0072] As can be seen from Figure 8(c), the Ti 2p binding energy peak of the CSD@HTS-1 sample significantly shifts to 459.62 eV, compared to 460.33 eV of the HTS-1 sample. This indicates that the density of the Ti 2p core electron cloud is reduced, which is presumably due to the mutual attraction between the electron clouds of nickel and titanium, thereby activating the active sites of the catalyst. The Ti2p XPS spectra of the samples of Example 1 and Comparative Examples 1, 2, and 3 are shown in Figure 8(c). The skeleton titanium (Ti 4+ ) has a binding energy peak at about 460 eV, but not skeleton titanium (Ti 6+ ) is located at 457.9eV. Compared with the HTS-1 sample (460.33eV), the Ti 2p binding energy peak of the CSD@HTS-1 sample significantly shifts to the right to 459.62eV, indicating that the Ti2p core electron cloud density is reduced. This is due to the mutual attraction between the electron clouds of nickel and titanium, which activates the active sites of the catalyst.

[0073] In summary, the XPS analysis results show that although the overall nickel loading is similar, the nickel in the CSD@HTS-1 sample is highly dispersed inside the molecular sieve, and there is a strong electron cloud interaction between nickel and titanium. This interaction is most significant in CSD@HTS-1 and may help activate the active sites of the catalyst.

[0074] like Fig. 9 As shown in the figure, the hydrogen reduction (H2-TPR) results of the samples prepared in Example 1 and Comparative Examples 2 and 3 show that the existence state of nickel in different samples is significantly different: nickel exists in the form of larger particles in the GR@HTS-1 sample, nickel exists in the form of smaller particles in the IMP@HTS-1 sample, and the nickel species in the CSD@HTS-1 sample is highly stabilized and dispersed by the zeolite framework, making it difficult to reduce within the temperature measurement range.

[0075] like Fig.10 As shown, the ultraviolet diffuse reflectance spectrum (UV-vis) shows significant differences in the presence of nickel in each sample. The absorption peak at 210nm represents the presence of framework titanium in the sample, the absorption peak at 260nm represents non-framework titanium substances, and the absorption peak at 314nm represents non-framework nickel substances and anatase. At the 260nm absorption peak, the absorption intensity of the CSD@HTS-1 sample is higher than that of the HTS-1. This is because the nickel in the CSD@HTS-1 sample replaces part of the framework titanium in the titanium silicalite MFI framework, resulting in the conversion of framework titanium to non-framework titanium and anatase, indicating that nickel in the CSD@HTS-1 sample is more inclined to exist in a dispersed state inside the titanium silicalite and affects the state of titanium. In the IM@HTS-1 and GR@HTS-1 samples, the non-framework titanium did not increase significantly. These samples have a wider absorption band in the range of 250-350nm. This is due to the Ni 2 O in + 2 -(2p)→Ni 2 +(3d) charge transfer indicates the presence of larger NiO particles, indicating that nickel mainly exists on the surface in the form of larger NiO particles without significantly affecting the state of skeleton titanium.

[0076] As shown in Table 2, it can be seen from the physical adsorption results that the nickel in the CSD@HTS-1 sample exists in the form of skeleton nickel, so its pore structure has not changed significantly. The mesopores and micropores of the IM@HTS-1 sample are significantly reduced, indicating that the nickel is mainly loaded on the surface of the molecular sieve. The pore structure of the GR@HTS-1 sample has not changed significantly, indicating that the loading method of mechanical grinding and mixing is just to mix nickel oxide with the HTS-1 molecular sieve, and almost no nickel oxide particles are introduced into the pores of the molecular sieve.

[0077] As shown in Table 3, the results of phenol hydroxylation reaction of different samples show that the performance of CSD@HTS-1 sample in phenol hydroxylation reaction is better than other loading methods, and its phenol hydroxylation conversion rate reaches 30.85%, which is significantly higher than 24.77% of HTS-1, and the selectivity of hydroquinone is also increased from 54.23% to 60.46%. In contrast, the conversion rate of GR@HTS-1 sample is reduced due to the blocking of pores by nickel oxide particles, and the selectivity of hydroquinone is 49.38%. Although the catalytic performance of IM@HTS-1 sample is improved by loading nickel through wet impregnation and coprecipitation, the cycle performance is poor due to problems such as uneven nickel loading and large particles. The synergistic effect of nickel and titanium active sites in CSD@HTS-1 sample and the existence form of nickel in titanium silicalite framework are the key to improving catalytic performance.

[0078] As shown in Table 4, the cyclic performance of the CSD@HTS-1 sample in the phenol hydroxylation reaction shows that the catalyst performance remains stable after 5 cycles.

[0079] In summary, in the CSD@HTS-1 sample prepared by tetrapropylammonium hydroxide combined with coordination complex method in Example 1, nickel exists in the form of skeleton nickel, and this state of existence significantly affects the catalytic performance. The high dispersion of nickel and the strong interaction with titanium effectively activate the active sites of the catalyst, and improve the conversion rate of phenol hydroxylation reaction (30.85%) and the selectivity of hydroquinone (60.46%). In contrast, in other samples, nickel mainly exists on the surface in the form of nickel oxide particles, resulting in pore blockage and decreased catalytic performance, which proves the superiority of nickel skeleton loading method in improving catalytic performance. In addition, the CSD@HTS-1 sample has good recycling performance in the phenol hydroxylation reaction.

[0080] Comparative Example 4

[0081] In this example, the catalytic performance of the characteristic samples prepared in the present invention is mainly compared with that of commercial catalysts, and the evaluation method is as follows: the reaction is carried out in a 100 mL double-necked round-bottom flask equipped with a reflux condenser, and a certain amount of commercial catalyst (200 mg), deionized water (10 mL), and phenol (2 g) are added respectively. After being heated to 80° C. in a constant temperature oil bath and maintained for a period of time, H2O2 (720 μL; the molar ratio of phenol to H2O2 is 3:1) is added. After reacting for different times, the liquid product is aspirated, extracted with ethyl acetate, and an appropriate amount of the upper organic extract phase is taken for analysis using a gas chromatograph (GC-Agilent8890) equipped with a 30 m capillary column (HP-5) and a FID detector.

[0082] As can be seen from Table 5, the CSD@HTS-1 catalyst of the present invention has a higher phenol conversion rate, a higher selectivity for diphenol, and does not contain phenol as a by-product.

[0083] Table 1. Component analysis of samples prepared by different methods

[0084]

[0085] In the table, a is the ICP analysis result; b is the XPS analysis result.

[0086] Table 2. Physical adsorption results of samples prepared by different methods

[0087]

[0088] In the table, Specific surface area is the specific surface area, S BET is the total specific surface area, S micro is the micropore specific surface area, S external is the external specific surface area, Specific pore volume is the pore volume, V micro is the micropore volume, V meso is the mesopore volume, V total is the total pore volume.

[0089] Table 3. Comparison of catalytic performance of phenol hydroxylation to hydroquinone synthesized by different methods

[0090]

[0091] Table 4. Catalytic performance of CSD@HTS-1 sample for phenol hydroxylation to produce hydroquinone

[0092]

[0093] Table 5. Comparison of catalytic performance of CSD@HTS-1 sample and commercial phenol hydroxylation to produce diphenol

[0094]

[0095] The above examples fully illustrate that the skeleton nickel-doped TS-1 molecular sieve prepared in the present invention has excellent activity, anti-coking ability and recycling performance.

Claims

1. A method for preparing a framework nickel-doped TS-1 type molecular sieve catalyst, characterized in that: The method uses TS-1 titanium silicalite raw powder prepared from cheap raw materials as the initial raw material, and introduces nickel cations into the TS-1 molecular sieve framework through nickel ion coordination complexation combined with tetrapropylammonium hydroxide hydrothermal treatment, and forms a hollow cavity inside the molecular sieve crystal; tetrapropylammonium hydroxide promotes the dissolution and recrystallization of the TS-1 titanium silicalite to form closed or open mesopores, and embeds nickel ions into the molecular sieve framework.

2. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 1, characterized in that: The method comprises the following steps: 1) adding TS-1 titanium silicon molecular sieve raw powder into a mixed solution of deionized water and tetrapropylammonium hydroxide, wherein the molar ratio of tetrapropylammonium hydroxide to deionized water is 1:1000-1:50, and the mass ratio of TS-1 titanium silicon molecular sieve raw powder to the mixed solution is 1:5-1:50; 2) adding a nickel source protected by a complexing agent, wherein the molar ratio of the nickel source to the complexing agent is 1:0.1-1:10; 3) pouring the mixture into a reactor, and subjecting it to hydrothermal treatment at 150-180°C for 24-72 hours; and 4) cooling the reactor to room temperature, centrifuging, washing, drying and roasting to obtain a product.

3. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 2, characterized in that: Preferably, the molar ratio of tetrapropylammonium hydroxide to deionized water is 1:1 to 1:

30.

4. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 2, characterized in that: Preferably, the molar ratio of the nickel source to the complexing agent is 1:0.2 to 1:5, the nickel source used is one or more of nickel sulfate, nickel phosphate, nickel nitrate, nickel acetate, nickel chloride, and nickel carbonate; the complexing agent used is one or more of ethylenediamine, diethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, hexamethylenediamine, and polyethylenepolyamine.

5. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 1, characterized in that: The cheap raw materials include: the template agent is tetrapropylammonium bromide, the titanium source is one or more of tetrabutyl titanate, tetraisopropyl titanate, titanium sulfate, titanium tetrachloride or titanium trichloride, the silicon source is at least one of water glass, silica gel and silica sol, and the alkali source is an organic amine, including at least one of ammonia water, methylamine, ethylamine, ethylenediamine, diethylamine, triethylamine, propylamine, n-butylamine and hexamethylenediamine.

6. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 5, characterized in that: The process of preparing TS-1 titanium silicalite raw powder using cheap raw materials is as follows: first, deionized water, tetrapropylammonium bromide and organic amine are mixed evenly, and then a silicon source is added dropwise, and stirring is continued until the solution is clarified and uniform, and then a titanium source is added and stirred to form a clarified mixed solution; then, a titanium silicalite precursor dry gel containing original zeolite units, or nano-scale TS-1 titanium silicalite seed crystals, or a titanium silicalite precursor solution is added, and the mixture is transferred to a high-pressure reactor with a polytetrafluoroethylene liner, and crystallized at 130-170°C for 12-48 hours; after the reactor is cooled to room temperature, the product is obtained by centrifugation, washing, drying and roasting; wherein the molar ratio of tetrapropylammonium bromide to the silicon source is less than 0.05, and the content of the titanium silicalite precursor in the titanium silicalite precursor dry gel containing original zeolite units, the nano-scale TS-1 titanium silicalite seed crystals or the titanium silicalite precursor solution is 5-20wt%.

7. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 5, characterized in that: In the TS-1 titanium silicalite raw powder, the crystal size of the TS-1 titanium silicalite is 150 nanometers to 800 nanometers, and the silicon-titanium atomic ratio is 20 to 200.

8. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 2, characterized in that: In nickel-doped TS-1 titanium silicon molecular sieve, the nickel content in the molecular sieve crystal is 0.01-5wt%, and the titanium content is 0.01-2.5wt%. Nickel exists in the form of cations, partially replacing titanium ions in the framework, reducing the charge density around the titanium ions and weakening the surface acidity.

9. The method for preparing the skeleton nickel-doped TS-1 type molecular sieve catalyst according to claim 2, characterized in that: The prepared nickel-doped TS-1 titanium silicon molecular sieve has a b-axis oriented flaky single crystal structure, no intergrowth twins, and a small crystal size of 150 nanometers to 800 nanometers. In addition to intrinsic micropores, the molecular sieve crystal also has closed or open mesopores with a micropore volume of 0.10 to 0.20 cm 3 ·g -1 , the mesopore volume is 0.10~0.50cm 3 ·g -1 .

10. Use of the skeleton nickel-doped TS-1 type molecular sieve catalyst according to any one of claims 1 to 9, characterized in that: The framework nickel-doped TS-1 molecular sieve catalyst exhibits excellent activity, anti-coking ability and recycling performance in olefin epoxidation, phenol oxidation, aromatic hydrocarbon hydroxylation, ketone ammoxidation, alkane partial oxidation or alcohol partial oxidation reactions, which is beneficial to mass transfer and improves catalytic efficiency.

Citation Information

Patent Citations

  • Preparation of porous crystalline synthetic material comprised of silicon and titanium oxides

    US4410501A

Cited By

  • Structured TS-1 titanium silicalite molecular sieve catalyst capable of being regenerated in situ by hydrogen peroxide as well as preparation method and application of structured TS-1 titanium silicalite molecular sieve catalyst

    CN121775904A